(untitled) (International Journal of Engineering and Computer Science, 2014)
Generally in industries there are traditional network communications like RS232,RS485,etc. which are limited for short distances. Data acquisition based on single chip has limited processing capacity and real time reliability. With development in Arm processor, efficient data acquisition and control in various fields can be achieved. Remote I/O data acquisition system developed in this project measures temperature, humidity, gas using WSN(wireless sensor networks) technology. WIFI Technology is a proficient used by mobiles, workplaces, home an d computer system all around the world. Wifi technology is a spectrum radio technology and OFDM radio technology therefore it is an alternative of wireless LAN. WIFI technology based on the IEEE 802.11 and wifi technology alliance so we can say that it is a synonym of IEEE802.11.This system is developed using ARM9(S3C2440A) hardware platform combined with WI-FI network. IT consists of two nodes one Transmitter node and one Receiver node. The transmitter node acquires sensors information ,process data and transmit it through WI-FI to Receiver node. The receiver node receives data from sensors node which is implemented on ARM9,process it and retransmits the controlling signal information via WI-FI communication and also display the sensor information on PC based GUI implemented using Mat Lab. The keil IDE software will be used to build the hex file for these C programs.